Financial Technology Analysis on the Development of Micro Business in the Sei Sikambing B Market, Sub-District Medan Sunggal City of Medan - Sativa, Annisa Yasmin; Sari, Wahyu Indah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this study is to identify the influence of financial technology (Fintech) on the development of micro-enterprises in the Sei Sikambin B market, Medan Sunggal District, Medan City. MSMEs, which consist of micro and medium businesses, have a large share in economic activities. The study used a quantitative descriptive method through the use of linear regression analysis techniques.E-Wallet, Income, Financial Satisfaction, and Financial Technology (Fintech). The results of the study indicate that PEOU, Financial Satisfaction, Income, and Fintech have a significant influence on the development of micro-enterprises, while E-Wallet does not show a significant influence. This study underlines the importance of fintech in increasing efficiency and satisfaction in MSME transactions, as well as the need for supervision to optimize the benefits of financial technology for micro-entrepreneurs